Efficacy, Safety, and Durability of Long-Acting Cabotegravir and Rilpivirine in Adults With Human Immunodeficiency Virus Type 1 Infection: 5-Year Results From the LATTE-2 Study. (25th August 2021) - Smith, Graham H R; Henry, W Keith; Podzamczer, Daniel; Masiá, Maria Del Mar; Bettacchi, Christopher J; Arasteh, Keikawus; Jaeger, Hans; Khuong-Josses, Marie-Aude; Montes-Ramírez, Maria Luisa; Stellbrink, Hans-Jürgen; Yazdanpanah, Yazdan; Richmond, Gary J; et al.
Abstract: Background: In the Long-Acting Antiretroviral Treatment Enabling Trial 2 (LATTE-2) phase 2b study, long-acting (LA) injectable cabotegravir + rilpivirine dosed every 8 weeks (Q8W) or every 4 weeks (Q4W) demonstrated comparable efficacy with daily oral antiretroviral therapy (ART) through 96 weeks in ART-naive adults with human immunodeficiency virus type 1 (HIV-1). Here we report efficacy, tolerability, and safety of cabotegravir + rilpivirine LA over approximately 5 years. Methods: After 20 weeks of oral cabotegravir + abacavir/lamivudine, participants were randomized to cabotegravir + rilpivirine LA Q8W or Q4W or continue oral ART through the 96-week maintenance period. In the extension period through week 256, participants continued their current LA regimen (randomized Q8W/Q4W groups) or switched from oral ART to Q8W or Q4W LA therapy (extension-switch groups). Endpoints assessed included proportion of participants with HIV-1 RNA <50 copies/mL (Snapshot algorithm) and adverse events (AEs). Results: At week 256, 186 of 230 (81%) participants in randomized Q8W/Q4W groups and 41 of 44 (93%) participants in extension-switch groups had HIV-1 RNA <50 copies/mL. No protocol-defined virologic failures occurred after week 48. Injection wsite reactions infrequently resulted in discontinuation (4 [2%] and 1 [2%] participants in randomized Q8W/Q4W and extension-switch groups, respectively). Three participants in randomized Q8W/Q4W groups experienced drug-related serious AEs, including 1 fatal serious AE (Q4W group); none occurred in extension-switch groups. Of 25 participants with AEs leading to withdrawal, 20 were in the randomized Q4W group; no AE leading to withdrawal occurred in >1 participant. Conclusions: Cabotegravir + rilpivirine LA exhibited long-term efficacy and tolerability, demonstrating its durability as maintenance therapy for HIV-1 infection. Clinical Trials Registration. NCT02120352.